A Comprehensive Guide to Perioperative Management and Operative Technique for Robotic Cystectomy with Intracorporeal Urinary Diversion. Issue 2 (April 2017) - Tan, Wei Shen; Lamb, Benjamin W.; Sridhar, Ashwin; Briggs, Timothy P.; Kelly, John D.
Robotic-assisted radical cystectomy (RARC) represents an evolution of open radical cystectomy (ORC) with the aim of reducing patient morbidity and improving return to normal function, whilst maintaining oncological equivalence. RARC is gaining popularity, especially in high-volume centres, although there remains a lack of level 1 evidence to demonstrate any superiority of RARC over ORC. All previously reported studies that randomised ORC and RARC have utilised a technique for RARC requiring a conversion to open surgery for urinary diversion. Conversion to open surgery invariably masks the benefits of a truly minimally invasive approach. Moreover, such studies tend to report a small sample size, likely reflecting early surgical experience that may contribute to the lack of observed benefit. Nonetheless, it is established that short-term oncological outcomes following RARC are comparable to those after ORC. It is likely that the benefits of RARC are only observed in cases wherein intracorporeal urinary diversion (iRARC) is performed by a surgical team with high volume experience, which will minimise morbidity and maximise early return to normal function. In this review, we will discuss a holistic approach to iRARC, including patient selection, perioperative optimisation, the surgical technique for iRARC with urinary diversion reconstruction, the use of enhanced recovery protocol, oncological outcomes and perioperative complications.